(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
As per ancient Ayurvedic scholars for getting a desirable outcome of any medication, it should be precisely analysed before prescribing to the patient. There are numbers of classical formulations successfully practiced by Ayurvedic physicians for treating various ailments but in maximum cases there is lack of data regarding their details mechanism of action. Such one multidrug classical formulation is Gandhaka rasayana which is widely practiced Ayurvedic formulation. Gandhaka rasayana have been used in Ayurvedic Rasashastra to treat various types of diseases related to Tvak, Mandhagni, various Srotas. It is a time tested formulation used by Ayurvedic practitioners for correcting Kushta, Indralupta, Vatarakta, Palitya, Dushta vrana, Arumsika etc. Modern scientific world needs explanation and logic behind the mode of action of Gandhaka rasayana with respective to each particular disease. This review is an attempt to explain multiple mode of action of Gandhaka rasayana in various diseases on analysing properties of ingredients. Analysis of mode of action gives deep insight about use of formulation with a better understanding.